1995
DOI: 10.1002/bem.2250160603
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of magnetic fields from domestic appliances and corresponding induced current densities in an anatomically based model of the human head

Abstract: Magnetic fields emitted by electric appliances such as razors, hair dryers, and drills were measured in the frequency domain. Results show the presence of high-frequency components (up to 96 kHz for razors, up to 3.4 kHz for hair dryers, and up to 8.6 kHz for drills) in the harmonic content of the fields. The measured fields were used to calculate the induced current densities in an anatomically based model of the human head (resolution 1.31 cm) by using the impedance method. The harmonic field contribution to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, these values did not take into account the contribution of harmonics, thus are likely to underestimate the total induced current density. Maximum induced current densities of 87.6 μA/m 2 were also reported for razors (N = 6), and 16.9 μA/m 2 for drills (N = 3) for the dominant spectral component (Tofani et al, 1995). Apart from one of the hair dryers assessed by Cheng et al, all of these current densities are much lower than the endogenous levels in the body, which are reported to be of the order of 1 mA/m 2 (Cheng et al, 1995;NRC, 1997).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, these values did not take into account the contribution of harmonics, thus are likely to underestimate the total induced current density. Maximum induced current densities of 87.6 μA/m 2 were also reported for razors (N = 6), and 16.9 μA/m 2 for drills (N = 3) for the dominant spectral component (Tofani et al, 1995). Apart from one of the hair dryers assessed by Cheng et al, all of these current densities are much lower than the endogenous levels in the body, which are reported to be of the order of 1 mA/m 2 (Cheng et al, 1995;NRC, 1997).…”
Section: Discussionmentioning
confidence: 60%
“…In relation to household appliances held close to the head, Cheng et al reported maximum induced current densities (with (5 mm) 3 resolution phantoms) of 47 μA/m 2 and 3400 μA/m 2 from hair dryers (5 cm from head, N = 2) at 60 Hz (Cheng, Stuchly, DeWagter, & Martens, 1995), and Tofani et al reported maximum induced current density (with (13 mm) 3 resolution phantoms) of 10.9 μA/m 2 at 50 Hz (2 cm from head, N = 3) (Tofani, Anglesio, Ossola, & d'Amore, 1995). Both of these studies included CSF and thus could be up to 10 times larger than brain tissue induced current density.…”
Section: Discussionmentioning
confidence: 99%